The assessment of change in human heat stress risk in Brazil projected by the CMIP6 models - Laila K Gohar; Dan Bernie; Damian Wilson; Kate Willett; Richard Betts (Environmental Research Communications, 2025)
Climate change in Brazil is expected to increase the occurrences of heat related conditions hazardous to human health. Thresholds in the environmental conditions leading to heat stress in humans are projected to be exceeded for long periods of the year across large parts of the country. We analyse future changes in the frequency of exceeding heat stress related thresholds during the hottest part of the day as measured by the Wet Bulb Globe Temperature (WBGT) and using the CMIP6 climate projections. Thresholds that require significant reduction in physical activity are estimated to be exceeded for most of northern Brazilian if the increase in global temperature reaches 2 °C. These exceedances are projected to occur for the hottest part of the day for at least four months of the year. Reducing global temperature rise to 1.5 °C would lessen the impact seen in the northern states. If the temperature rise exceeds 3 °C, then almost the entire country at some point in the year will have levels of WBGT that would pose a high risk to health for people undertaking physical activity. Furthermore, 8% of the population will be affected for almost half of the year. The states of Amazonas, Amapa, Acre, Maranhao, Para and Roraima are most prone to experiencing high levels of WBGT and will be the first to experience WBGT levels that are too high for intense physical activity for more than 9 months if global temperature reaches 3 °C. High levels of WBGT will have significant impact on workers in rural areas. Adaptive policies for the agricultural areas of Brazil will need to consider the impact of heat stress rendering large regions of the country unsuitable for outdoor work for large parts of the year. This will be true even at global warming levels of 2 °C for northern and central Brazil.